2009
DOI: 10.1080/13697130802521282
|View full text |Cite
|
Sign up to set email alerts
|

Age at menopause and factors associated with attainment of menopause in an urban community in Ibadan, Nigeria

Abstract: Efforts should be made to provide education about the menopause to all women in their respective communities, especially to those who are approaching their fifth decade and who have no formal education, to better prepare them for this change of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 51 publications
5
24
1
Order By: Relevance
“…The mean age of postmenopausal women in this study is in line with that in most previous studies, which reported that most women have become menopausal above the age of 55 years (17, 18). The mean BMI of the postmenopausal women, however, is an important cause for concern because the majority of the participants were in the overweight category.…”
Section: Discussionsupporting
confidence: 92%
“…The mean age of postmenopausal women in this study is in line with that in most previous studies, which reported that most women have become menopausal above the age of 55 years (17, 18). The mean BMI of the postmenopausal women, however, is an important cause for concern because the majority of the participants were in the overweight category.…”
Section: Discussionsupporting
confidence: 92%
“…Occupation may be a factor correlated with educational level, as people with lower education tend to be manual workers. Additionally, both education and occupation have been found to be determinants of household income; therefore, general nutritional status, standard of living and access to healthcare services may contribute to the relationship between type of work and menopausal age [31]. …”
Section: Discussionmentioning
confidence: 99%
“…The health concerns linked with the use of hormone replacement therapy (HRT)[9] and other drugs for prevention and treatment of menopausal symptoms[10] emphasizes the need to identify the modifiable risk factors and role of alternative medicine like phytoestrogens,[11] isoflavones,[12] acupuncture,[13] and yoga. [14] ANM is influenced by various determinants[15161718] like genetic, demographic, socioeconomic, dietary, reproductive, and behavioral; of which some are modifiable like lifestyle and dietary.…”
Section: Introductionmentioning
confidence: 99%